Software development for small details production warehouse automated system - Nevliudov, I.; Maksymova, S.; Nevliudova, V.; Vzhesniewski, M.; Klymenko, O. (My University, 2023)
The development of science and technology constantly sets new requirements for modern production. It should become more flexible and quickly adapt to new types of products. This leads to the need for a structured, easily understandable and convenient organization of storage of goods. Modern software will allow you to expand the supply chain, establish inventory management, processing and fulfillment of orders in accordance with modern procurement methods, will ensure the availability of all stocks in real time - with the help of personal computers, or even mobile devices.
Keywords: inventory management